Pengaruh Capital Adequacy Ratio (CAR) Dan Non Performing Loan (NPL) Terhadap Return On Equity (ROE) Pada Bank Umum Swasta Nasional Devisa Yang Terdaftar Di BEI (Bursa Efek Indonesia) - Novi Lestari; Rissa Mardiana (Jurnal Ekonomi dan Bisnis, 2022)
This research title is The Effect of Capital Adequacy Ratio (CAR) and Non Performing Loans (NPL) on Return On Equity (ROE) at Foreign Exchange National Private Commercial Banks listed on the Indonesia Stock Exchange for the 2011-2016 period. The sample used in this research is the Annual Financial Report of Foreign Exchange National Private Commercial Banks listed on the Indonesia Stock Exchange for the 2011-2016 period using a purposive sampling method, in order to obtain 114 sample data from 19 National Foreign Exchange Private Commercial Banks in the observation period (2011-2016) ). The type of data used is secondary data obtained from published financial reports and downloaded through the official website of the Indonesia Stock Exchange. The analytical method used is Multiple Linear Regression with a significance level of 0.05. The results of the analysis show that partially only NPL has a significant negative effect on ROE, while CAR has no effect on ROE. Simultaneously the CAR and NPL variables have a significant effect on ROE.